Quality of Life in Portuguese Municipalities: A Multidimensional Approach - Dionísio, Andreia; Rego, Maria Conceição; Sequeira, Teresa (Economy of Regions, 2023)
The estimation of the level of development of a territory is an issue that has had different approaches and methodologies. If the first attempts were associated with determining the income generated and retained by the territory, the most recent indicators of quality of life or well-being are based on a multidimensional concept, improved by adding other dimensions including several variables. On the other hand, despite the statistical difficulties, analysis of smaller geographic units is closer to reality, allowing researchers to draw relevant and effective final considerations. Focusing on the case of Portugal mainland, an old country with strong and persistent development asymmetries, this work sought to examine the similarities and differences in various dimensions of the concept of quality of life, in the positioning of the chosen territorial units, the municipalities. Then, after collecting recent annual variables at the municipality level, data were processed using multivariate analysis. The construction of clusters revealed affinities between the municipalities. The results obtained show the asymmetries of development and well-being in the national territory, and their disaggregation, both in terms of the multiple dimensions under analysis and in terms of the municipalities. The study offers a greater and deeper understanding of the regional reality and consequently can favour the efficiency of cohesion policies.